Transcranial Electrical Stimulation to Enhance Cognitive Performance of Healthy Minors: A Complex Governance Challenge - Schuijer, Jantien W.; de Jong, Irja M.; Kupper, Frank; van Atteveldt, Nienke M. (Frontiers in Human Neuroscience, 2017)
An increasing number of healthy adolescents are consuming products that can enhance their cognitive performance in educational settings. Currently, pharmaceuticals is the most widely discussed enhancement method in the literature, but new evidence suggests that other methods based on Transcranial Electrical Stimulation (TES) also have potential as cognitive enhancer. Just like pharmaceutical enhancers, the availability and education-related use of TES-devices raise a broad range of ethical, legal and societal issues that need to be addressed by policy-makers. Few studies, however, have specifically explored these issues in relation to child wellbeing. In this narrative review with systematic search, we describe the issues for child wellbeing that could arise from the availability and education-related use of TES-based enhancers by healthy minors. We demonstrate that the issues form a complex web of uncertainties and concerns, which are mainly incited by two factors. First is the high level of factual uncertainty due to gaps in empirical evidence about the exact working mechanisms and efficacy of TES. Moreover, a lack of insight into the technique’s (long-term) effects on healthy developing brains, and uncertainties about potential cognitive trade-offs have fueled concerns about the technique’s safety and impact. The second factor that contributes to the complexity of issues is the presence of moral diversity in our society. Different opinions exist on whether a certain enhancement effect would be desirable and whether potential risks would be acceptable. These opinions depend on one’s moral perspective, and the way one interprets and weights values such as the child’s autonomy and authenticity. The challenge for proper governance resides in the design of an appropriate framework that is capable of balancing the different moral perspectives in society, while recognizing the uncertainties that still exist. We therefore argue for a responsible innovation approach, which encourages an adaptive attitude towards emerging knowledge and dynamic societal values, to deal with the identified issues regarding TES-based enhancement appropriately.